Thermoformed composite fiber, preparation method and controllable degradation filter stick

By using the skin core structure of thermoformed composite fibers in the smoke filter rod, the problem of uneven degradation caused by direct contact between the catalyst and the cellulose acetate tow is solved, and the controlled release of the catalyst and the rapid degradation of the filter rod are achieved, ensuring that The stability of cigarette odor and usage effect.

CN119174517APending Publication Date: 2024-12-24NANTONG CELLULOSE FIBERS CO LTD +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411010098.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The catalyst of the existing smoke filter rod is in direct contact with the cellulose acetate tow, resulting in uneven degradation, affecting the cigarette's odor and usage effect, and the alkaline material distribution during processing is uneven, affecting the overall performance of the filter rod.

Method used

Using thermoformed composite fibers, the core layer and cortical structure are formed by melt extrusion processing. The core layer is embedded with a catalyst, and the cortical layer is wrapped with a water-soluble or hydrophilic polymer to avoid direct contact and co-extrusion or coating by melt. The application method forms the skin core structure fibers to ensure the even distribution and protection of the catalyst.

Benefits of technology

The controlled release of the catalyst is achieved, the rapid degradation of cellulose acetate is promoted, the odor absorption and structural integrity of the filter rod is protected, the stability of the cigarette is ensured, and the rapid degradation is achieved after being discarded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119174517A_ABST
    Figure CN119174517A_ABST
Patent Text Reader

Abstract

The invention relates to a thermoformed composite fiber, a preparation method and a controllable degradation filter stick, the composite fiber comprises a fiber formed by melt extrusion processing, and the fiber contains a catalyst for catalyzing deacetylation of cellulose acetate. The composite fiber further comprises a skin layer laid on the fiber, and a water-soluble polymer or a hydrophilic polymer is coated on the surface of the fiber to serve as the skin layer to protect the catalyst. And the composite fiber is embedded in the filter stick. The invention also provides a preparation method of the corresponding composite fiber, which comprises the following steps: uniformly mixing the fiber material and the catalyst material in the form of powder, carrying out melt extrusion by using a twin-screw extruder to process the fiber as the core layer, and then coating a layer of polymer on the surface of the core layer. The core layer is coated with a layer of water-soluble polymer or hydrophilic polymer as a skin layer to protect the core layer and control release of the degradation catalyst, after the filter stick is used and discarded, water in the environment dissolves the skin layer, the degradation catalyst of the core layer is released, and degradation of the filter stick is accelerated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of manufacturing filter rods for cigarettes, and in particular to a thermoformed composite fiber, a preparation method and a controllably degradable filter rod. Background Art

[0002] At present, the main material of filter rods for cigarettes is cellulose acetate, which is a material prepared by acetylation of cellulose as raw material. It can meet the requirements of compost degradation, but its degradation rate is slow in the natural environment. CN116133537A discloses a degradable cigarette filter, which contains cellulose ester and includes a catalyst containing alkaline materials, enzyme materials or a combination thereof, which can promote the degradation of filter rods. CN 116322382 A discloses a filament belt containing cellulose acetate and filler, which can be expanded and formed into a filter rod to promote the degradation of cellulose acetate. CN 112375259 A invented a polymer composition containing an alkaline additive, which generally shows enhanced biodegradability.

[0003] However, the catalyst of the filter rod prepared by the above method may be in direct contact with the cellulose acetate tow, and may be degraded during the commodity circulation stage, affecting the use effect of the commodity. The above patent involves the method of using water-soluble polymers but does not mention the method of adding alkaline materials. If the alkaline materials are added by sprinkling and adsorption, the alkaline materials will be unevenly distributed and easily scattered during the processing, making the processing inconvenient. Moreover, the catalyst added by a simple method will be directly exposed and in contact with the filter rod, affecting the taste of the cigarette, which is unacceptable. Summary of the invention

[0004] Based on this, the purpose of the present invention is to provide a thermoformed composite fiber, a preparation method and a controllable degradation filter rod, which can control the release rate of the catalyst through the composite fiber in the filter rod, thereby regulating the hydrolysis and degradation process of the filter rod for cigarettes. The present invention can avoid direct contact between the catalyst and the cellulose acetate tow, protect the function and structural integrity of the filter rod before use, and ensure that the catalyst does not interfere with the taste of the cigarette during the smoking process. After the filter tip processed with this filter rod is discarded in the natural environment, the catalyst can be quickly released to promote the degradation of the cellulose acetate filter tip tow.

[0005] The above technical objectives of the present invention are achieved through the following technical solutions:

[0006] A first object of the present invention is to provide a thermoformable composite fiber, the fiber comprising a fiber processed by melt extrusion, the fiber containing a catalyst for catalyzing the deacetylation of cellulose acetate.

[0007] Furthermore, the composite fiber is a structural fiber with a core layer inside and a skin layer outside (referred to as skin-core structural fiber), and the implementation methods include but are not limited to coating the outer surface of the core layer with a water-soluble polymer or a hydrophilic polymer by solution dipping as a skin layer, or electrostatically adsorbing another material on the outside of the core layer fiber and then heating and solidifying it, or by melt co-extruding two different materials, or by melt extrusion processing hollow fibers and then siphoning another material to achieve protection of the core layer catalyst.

[0008] Optionally, the core layer fiber is a water-soluble polymer or a hydrophilic polymer that can be melt-extruded, and the water-soluble polymer includes but is not limited to one or more of polyvinyl alcohol, polyethylene glycol, carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyacrylic acid, polyacrylic acid salt, polysulfonic acid, polysulfonic acid, polyacrylamide, soluble starch, modified starch and cellulose acetate, preferably one or more of polyvinyl alcohol and polyethylene glycol; hydrophilic polymers include but are not limited to polylactic acid (PLA), cellulose acetate (CA) and polybutylene adipate terephthalate, etc.

[0009] Furthermore, the alcoholysis degree of polyvinyl alcohol is 70%-95%, and the viscosity is 3-30 cps, where the viscosity is measured by using a Brookfield type rotational viscometer at 20 degrees Celsius to measure a 4% aqueous solution of PVA; the molecular weight of polyethylene glycol can be 300-20000, preferably 800-12000.

[0010] Optionally, the catalyst powder has a particle size range of 10 nm-50 μm, preferably 500 nm-5 μm; the water-soluble polymer and polylactic acid (PLA) powder particle size range is 30 μm-300 μm, preferably 50 μm-100 μm, to ensure uniform mixing with the catalyst.

[0011] Optionally, the catalyst is an alkaline material with a pH value greater than 7, which can catalyze the deacetylation of cellulose acetate, and can be an alkaline inorganic substance, including but not limited to magnesium oxide, magnesium hydroxide, calcium oxide, alkaline aluminum oxide, calcium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, magnesium carbonate, calcium carbonate, sodium bicarbonate, potassium bicarbonate, potassium phosphate, sodium phosphate, magnesium phosphate, calcium phosphate, ammonium hydrogen phosphate, sodium sulfite, etc., one or a combination of more than one thereof; and / or

[0012] The catalyst may also be a basic organic small molecule compound, including but not limited to arginine, lysine, histidine, amino acid polypeptide, sodium citrate, potassium citrate, sodium acetate, potassium acetate, pyridine, morpholine, imidazole, methylamine, ethylamine, diethylamine, triethylamine, diisopropylamine, 1-acetylguanidine, one or more combinations thereof;

[0013] Preferred are magnesium oxide, magnesium hydroxide, calcium hydroxide and 1-acetylguanidine.

[0014] The above catalysts can be used alone or in combination of more than one.

[0015] The catalyst may also be one or a combination of more than one of an alkaline catalyst, an alkaline amino acid and an enzyme catalyst.

[0016] Optionally, the weight ratio of the catalyst in the core layer is determined according to the stability of the catalysis and polymer melt extrusion processing. Too high a content of the catalyst will lead to instability in the melt extrusion process and even serious solidification. The weight ratio is generally controlled to be 1%-50%, preferably 5%-30%, and more preferably 15%-25%. Optionally, the water-soluble polymer or hydrophilic polymer in the skin layer can be polyvinyl alcohol (PVA), polyethylene glycol (PEG), carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose, soluble starch, cellulose acetate, etc.

[0017] Optionally, a water-soluble polymer layer containing an added enzyme catalyst can be coated between the core layer and the cortex layer to play a synergistic role with the catalyst to improve the degradation of cellulose acetate. Preferably, the enzyme catalyst is one or a combination of glucan endoglucanase, glucan exoglucanase, glucosidase, cellulase (C1 enzyme, Cx enzyme, β-glucosidase), endocellulase, exocellulase, hemicellulase, amylase, protease or esterase.

[0018] The positions of the structural layer containing alkaline catalyst and the structural layer containing enzyme catalyst can be exchanged, such as placing the structural layer containing alkaline catalyst in the core layer and the structural layer containing enzyme catalyst in the outer layer; or placing the structural layer containing enzyme catalyst in the core layer and the structural layer containing alkaline catalyst in the outer layer. The advantage of doing so is to avoid the alkaline catalyst from destroying the activity of the enzyme catalyst. After the alkaline catalyst removes the substituent of cellulose acetate, the enzyme catalyst can be used to promote the cleavage and degradation of cellulose chains, thereby better exerting the synergistic effect of the alkaline catalyst and the enzyme catalyst.

[0019] The second object of the present invention is to provide a controllable degradation filter rod, wherein the composite fiber is embedded in the filter rod during the molding process, and embedded into a single-line, double-line, multi-line or multi-line structure as required, as shown in Figure 2. The filter rod is used as a section of the filter tip structure.

[0020] The third object of the present invention is to provide a method for preparing the above-mentioned composite fiber, wherein the core layer material and the catalyst are uniformly mixed in the form of solid powder, and processed into fibers as the core layer by melt extrusion through a twin-screw machine. The melt extrusion process can ensure that the catalyst is uniformly dispersed in the water-soluble polymer or hydrophilic polymer matrix, and the processing process is simple; then a layer of water-soluble polymer or hydrophilic polymer is coated on the surface of the core layer as a skin layer to protect the catalyst of the core layer, forming a skin-core structure fiber, or a skin-core structure is formed by co-extrusion, and the skin-core structure fiber is buried in a filter rod during the molding process. This fiber is buried in a filter rod to make a filter rod that can adjust the degradation rate.

[0021] Optionally, the twin-screw machine melt extrusion processing temperature is 100°C-200°C, the diameter of the melt extruded fiber is 0.1mm-1mm, preferably 0.2mm-0.5mm. The tensile strength of the fiber is greater than 0.1N / tex -1 .

[0022] Optionally, melt extruded fibers containing the catalyst serve as the core layer.

[0023] Optionally, the water-soluble polymer or hydrophilic polymer in the cortex is adjusted as needed;

[0024] Water-soluble polymers or hydrophilic polymers refer to polymers having a main chain containing hydrophilicity, such as ether bonds, secondary amine bonds, and / or containing hydrophilic side chains and end groups, such as hydroxyl groups, amino groups, carboxyl groups, sulfonic acid groups, and amide groups, including but not limited to one or more of polyvinyl alcohol, polyethylene glycol, carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyacrylic acid, polyacrylic acid salts, polysulfonic acid, polysulfonic acid salts, polyacrylamide, soluble starch, modified starch, etc.

[0025] The solubility of a water-soluble polymer in water is generally greater than 1%.

[0026] Polyvinyl alcohol is selected as the water-soluble polymer or hydrophilic polymer in the cortex, and its configuration requires an alcoholysis degree of 70%-95%, a viscosity of 3-30 cps, and a concentration of 3%-20% in the configured aqueous solution, preferably 5%-12%; or

[0027] Polyethylene glycol is selected as the water-soluble polymer or hydrophilic polymer in the cortex, and its molecular weight is required to be 300-4000, preferably 800-1200, and the concentration of the prepared aqueous solution is 10%-30%; or

[0028] One of carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose is selected as the water-soluble polymer or hydrophilic polymer in the cortex, and the configuration requires a viscosity range of 30-20000mPaS and an aqueous solution concentration of 0.5%-5%; or

[0029] Soluble starch is selected as the water-soluble polymer or hydrophilic polymer in the cortex, and its configuration requires that the concentration of the aqueous solution ranges from 3% to 10%.

[0030] Cellulose acetate is selected as the water-soluble polymer or hydrophilic polymer in the skin layer, and its configuration requires a viscosity range of 1.4-1.7 g / dL (6% acetone solution Ubbelohde viscometer test), a substitution degree range of 2.0-2.8, preferably 2.3-2.5. Cellulose acetate is dissolved in acetone and then coated on the outside of the core layer. The concentration of the acetone solution is 3%-20%, preferably 5%-10%. After the acetone is dried, a skin-core structure fiber is obtained.

[0031] The skin layer can also be processed with the core layer by melt co-extrusion, and the skin layer is directly coated on the outside of the core layer. The core layer is consistent with the above scheme, and the skin layer uses a water-soluble polymer or a hydrophilic polymer that can be melt-extruded, which can be polyvinyl alcohol (PVA), polyethylene glycol (PEG), carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose, soluble starch, cellulose acetate, etc.

[0032] Due to the adoption of the above technical solution, the beneficial effects of the present invention include:

[0033] The outer surface of the melt-extruded core layer loaded with the catalyst is coated with a water-soluble polymer or a hydrophilic polymer to form a fiber with a skin-core structure. The skin structure can well protect the catalyst. When the skin contacts the water in the environment, the skin is destroyed, and the catalyst loaded in the core layer can be released, or the catalyst passes through the protective layer by slow penetration.

[0034] The composite fiber is buried in the filter rod. After the filter rod is used and discarded, the water in the environment dissolves the cortex, releases the degradation catalyst of the core layer, and then promotes the degradation of the cellulose acetate tow. At the same time, the cortex prevents the catalyst of the core layer from directly contacting the cellulose acetate tow of the filter rod material. If the added catalyst directly contacts the cellulose acetate tow of the filter rod material, it may affect the odor absorption of the filter tip. The present invention uses the cortex as a protective layer to keep the filter tip from being disturbed by odor. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a curve diagram of the change of the degree of substitution of cellulose acetate in Examples 1-13 of the present invention over time.

[0036] Figure 2 is a schematic diagram of the structure of the controllable degradation filter rod of the present invention; wherein (a) is a schematic diagram of the skin-core structure fiber buried in the filter rod; and (b) is a schematic diagram of the structure of the skin-core structure fiber. DETAILED DESCRIPTION

[0037] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0038] <Preparation of Thermoformed Composite Fiber>

[0039] Example 1

[0040] PVA (KURARAY POVAL TM 5-74) is a water-soluble polymer with a viscosity of 4.2-5.0 cps and a degree of alcoholysis of 72.5%-74.5%, and a weight of 85 parts. Magnesium oxide with a particle size of 1 μm is used as a catalyst, and a weight of 15 parts.

[0041] After the two powders are evenly mixed, they are melt-extruded by a twin-screw machine at an extrusion temperature of 100°C-150°C. The stretching ratio is adjusted to control the diameter of the wire to 0.3mm. The wire is cooled by air and used as the core layer.

[0042] Cellulose acetate with a viscosity of 1.60 g / dL and a degree of substitution of 2.45 was prepared into an acetone solution with a concentration of 8%, and was evenly coated on the outside of the core layer as the skin layer.

[0043] Example 2

[0044] PVA (KURARAY POVAL TM 5-74) is a water-soluble polymer with a viscosity of 4.2-5.0 cps and a degree of alcoholysis of 72.5%-74.5%, and a weight of 80 parts. Magnesium oxide with a particle size of 1 μm is used as a catalyst, and a weight of 20 parts.

[0045] After the two powders are evenly mixed, they are melt-extruded by a twin-screw machine at an extrusion temperature of 100°C-150°C. The stretching ratio is adjusted to control the diameter of the wire to 0.3mm. The wire is cooled by air and used as the core layer.

[0046] Cellulose acetate with a viscosity of 1.60 g / dL and a degree of substitution of 2.45 was prepared into an acetone solution with a concentration of 8%, and was evenly coated on the outside of the core layer as the skin layer.

[0047] Example 3

[0048] PVA (KURARAY POVAL TM5-74) is a water-soluble polymer with a viscosity of 4.2-5.0 cps and a degree of alcoholysis of 72.5%-74.5%, and a weight of 80 parts. Magnesium oxide with a particle size of 1 μm is used as a catalyst, and a weight of 20 parts.

[0049] After the two powders are evenly mixed, they are melt-extruded by a twin-screw machine at an extrusion temperature of 100°C-150°C. The stretching ratio is adjusted to control the diameter of the wire to 0.3mm. The wire is cooled by air and used as the core layer.

[0050] Hydroxypropyl methylcellulose with a viscosity of 400 mps was used as a water-soluble polymer to prepare an aqueous solution with a concentration of 1.5%, and the aqueous solution was evenly coated on the outside of the core layer to serve as the skin layer.

[0051] Example 4

[0052] PVA (KURARAY POVAL TM 5-74) is a water-soluble polymer with a viscosity of 4.2-5.0 cps and a degree of alcoholysis of 72.5%-74.5%, and a weight of 80 parts. Magnesium oxide with a particle size of 1 μm is used as a catalyst, and a weight of 20 parts.

[0053] After the two powders are evenly mixed, they are melt-extruded by a twin-screw machine at an extrusion temperature of 100°C-150°C. The stretching ratio is adjusted to control the diameter of the wire to 0.3mm. The wire is cooled by air and used as the core layer.

[0054] Prepare a 10% aqueous solution of PVA 5-74 and evenly apply it on the outside of the core layer as the skin layer.

[0055] Example 5

[0056] PVA (KURARAY POVAL TM 5-74) is a water-soluble polymer with a viscosity of 4.2-5.0 cps and a degree of alcoholysis of 72.5%-74.5%, and a weight of 80 parts. Magnesium oxide with a particle size of 1 μm is used as a catalyst, and a weight of 20 parts.

[0057] After the two powders are evenly mixed, they are melt-extruded by a twin-screw machine at an extrusion temperature of 100°C-150°C. The stretching ratio is adjusted to control the diameter of the wire to 0.3mm. The wire is cooled by air and used as the core layer.

[0058] A 16% aqueous solution of PEG-1000 was prepared and evenly coated on the outside of the core layer of Example 1 to serve as the skin layer.

[0059] Example 6

[0060] PVA (KURARAY POVAL TM5-74) is a water-soluble polymer with a viscosity of 4.2-5.0 cps and a degree of alcoholysis of 72.5%-74.5%, and a weight of 80 parts. Sodium carbonate with a particle size of 1 μm is used as a catalyst, and a weight of 20 parts.

[0061] After the two powders are evenly mixed, they are melt-extruded by a twin-screw machine at an extrusion temperature of 100°C-150°C. The stretching ratio is adjusted to control the diameter of the wire to 0.3mm. The wire is cooled by air and used as the core layer.

[0062] Cellulose acetate with a viscosity of 1.60 g / dL and a degree of substitution of 2.45 was prepared into an acetone solution with a concentration of 8%, and was evenly coated on the outside of the core layer as the skin layer.

[0063] Example 7

[0064] PVA (KURARAY POVAL TM 5-74) is a water-soluble polymer with a viscosity of 4.2-5.0 cps and a degree of alcoholysis of 72.5%-74.5%, and a weight of 80 parts. Calcium hydroxide with a particle size of 1 μm is used as a catalyst, and a weight of 20 parts.

[0065] After the two powders are evenly mixed, they are melt-extruded by a twin-screw machine at an extrusion temperature of 100°C-150°C. The stretching ratio is adjusted to control the diameter of the wire to 0.3mm. The wire is cooled by air and used as the core layer.

[0066] Cellulose acetate with a viscosity of 1.60 g / dL and a degree of substitution of 2.45 was prepared into an acetone solution with a concentration of 8%, and was evenly coated on the outside of the core layer as the skin layer.

[0067] Example 8

[0068] PEG1000 with a particle size of 100 μm was used as the matrix, with a weight of 80 parts. Magnesium oxide with a particle size of 1 μm was used as the catalyst, with a weight of 20 parts.

[0069] After the two powders are evenly mixed, they are melt-extruded by a twin-screw machine at an extrusion temperature of 100°C-150°C. The stretching ratio is adjusted to control the diameter of the wire to 0.3mm. The wire is cooled by air and used as the core layer.

[0070] Cellulose acetate with a viscosity of 1.60 g / dL and a degree of substitution of 2.45 was prepared into an acetone solution with a concentration of 8%, and was evenly coated on the outside of the core layer as the skin layer.

[0071] Example 9

[0072] PEG1000 with a particle size of 100 μm was used as the matrix, with a weight of 80 parts. Calcium oxide with a particle size of 1 μm was used as the catalyst, with a weight of 20 parts.

[0073] After the two powders are evenly mixed, they are melt-extruded by a twin-screw machine at an extrusion temperature of 100°C-150°C. The stretching ratio is adjusted to control the diameter of the wire to 0.3mm. The wire is cooled by air and used as the core layer.

[0074] Cellulose acetate with a viscosity of 1.60 g / dL and a degree of substitution of 2.45 was prepared into an acetone solution with a concentration of 8%, and was evenly coated on the outside of the core layer as the skin layer.

[0075] Example 10

[0076] PLA with a particle size of 100 μm was used as the matrix, with a weight of 80 parts. Magnesium oxide with a particle size of 1 μm was used as the catalyst, with a weight of 20 parts.

[0077] After the two powders are evenly mixed, they are melt-extruded by a twin-screw machine at an extrusion temperature of 100°C-150°C. The stretching ratio is adjusted to control the diameter of the wire to 0.3mm. The wire is cooled by air and used as the core layer.

[0078] Cellulose acetate with a viscosity of 1.60 g / dL and a degree of substitution of 2.45 was prepared into an acetone solution with a concentration of 8%, and was evenly coated on the outside of the core layer as the skin layer.

[0079] Embodiment 11

[0080] PLA with a particle size of 100 μm was used as the matrix, with a weight of 80 parts. Calcium oxide with a particle size of 1 μm was used as the catalyst, with a weight of 20 parts.

[0081] After the two powders are evenly mixed, they are melt-extruded by a twin-screw machine at an extrusion temperature of 100°C-150°C. The stretching ratio is adjusted to control the diameter of the wire to 0.3mm. The wire is cooled by air and used as the core layer.

[0082] Cellulose acetate with a viscosity of 1.60 g / dL and a degree of substitution of 2.45 was prepared into an acetone solution with a concentration of 8%, and was evenly coated on the outside of the core layer as the skin layer.

[0083] Example 12

[0084] PVA (KURARAY POVAL TM 5-74) is a water-soluble polymer with a viscosity of 4.2-5.0 cps and a degree of alcoholysis of 72.5%-74.5%, with a weight of 80 parts. Arginine powder is used as a catalyst, with a weight of 20 parts.

[0085] After the two powders are evenly mixed, they are melt-extruded by a twin-screw machine at an extrusion temperature of 100°C-150°C. The stretching ratio is adjusted to control the diameter of the wire to 0.3mm. The wire is cooled by air and used as the core layer.

[0086] Cellulose acetate with a viscosity of 1.60 g / dL and a degree of substitution of 2.45 was prepared into an acetone solution with a concentration of 8%, and was evenly coated on the outside of the core layer as the skin layer.

[0087] Embodiment 13

[0088] PVA (KURARAY POVAL TM 5-74) is a water-soluble polymer with a viscosity of 4.2-5.0 cps and a degree of alcoholysis of 72.5%-74.5%, with a weight of 80 parts. 1-Acetylguanidine is used as a catalyst, with a weight of 20 parts.

[0089] After the two powders are evenly mixed, they are melt-extruded by a twin-screw machine at an extrusion temperature of 100°C-150°C. The stretching ratio is adjusted to control the diameter of the wire to 0.3mm. The wire is cooled by air and used as the core layer.

[0090] Cellulose acetate with a viscosity of 1.60 g / dL and a degree of substitution of 2.45 was prepared into an acetone solution with a concentration of 8%, and was evenly coated on the outside of the core layer as the skin layer.

[0091] Embodiment 14

[0092] PVA574 with a particle size of 100 μm was used as the matrix, with a weight of 80 parts. Calcium oxide with a particle size of 1 μm was used as the catalyst, with a weight of 20 parts.

[0093] After the two powders are evenly mixed, they are melt-extruded by a twin-screw machine at an extrusion temperature of 100°C-150°C. The stretching ratio is adjusted to control the wire diameter to 0.3mm.

[0094] Cross-linking occurs during the extrusion process and cannot be processed.

[0095] Comparative Example 1

[0096] PVA574 with a particle size of 100 μm was used as the matrix, with a weight of 100 parts, and melt-extruded by a twin-screw machine at an extrusion temperature of 100° C.-150° C. The stretching ratio was adjusted to control the filament diameter to 0.3 mm.

[0097] <Controllable degradation filter stick>

[0098] As shown in FIG2 , the fiber of the skin-core structure containing the catalyst prepared in the above embodiment is embedded in the cellulose acetate tow, and double-line embedding is adopted without adding other substances to make a filter rod. Take the above filter rod 45cm (cellulose acetate tow weighs 3g), add 80g, and stir at room temperature. The concentration of acetic acid released at different times is tested, and the degree of substitution of the corresponding cellulose acetate is calculated by the reduction method. The results are shown in Table 1. The degree of acetyl substitution of the undegraded cellulose acetate tow is 2.45. After hydrolysis and deacetylation, the degree of acetyl substitution decreases. Generally, the degradation rate of cellulose acetate with a degree of substitution higher than 2.1 is the slowest. As the degree of acetyl substitution decreases, the degradation rate increases. The degree of substitution lower than 2.1 can be rapidly degraded, that is, the hydrolysis process of acetyl is the rate-determining step of the degradation of cellulose acetate. This experiment mainly evaluates the hydrolysis rate at the front end of the degradation, and the hydrolysis rate is used as the basis for judging the degradation rate.

[0099] Table 1 - Changes of acetyl substitution degree of cellulose acetate tow in filter rods over time

[0100]

[0101]

[0102] In control example 1, no catalyst was added, and the degree of substitution of the cellulose acetate tow was basically unchanged. The degradation rate of cellulose acetate in Examples 6 and 12 was relatively slow, indicating that the weaker alkali-combined sustained-release effect effectively inhibited the degradation process. Example 7 can control the degradation of cellulose acetate relatively quickly. Example 10 can control the degradation at a uniform rate, because PLA has a better structure-retaining effect and can uniformly control the catalyst release process. Examples 9 and 11 can quickly promote cellulose degradation and can provide a solution that requires rapid degradation.

[0103] The present invention realizes the controlled release of the catalyst by adopting the melt extrusion method, and the appropriate method can be selected according to the customer's usage requirements; the fiber processing process of the present invention does not use solvents, and realizes the addition of catalysts in an economical and convenient way, ensuring the cleanliness of the filter rod processing process; at the same time, the quality stability of the filter rod before the cigarette is used can be guaranteed, and the filter rod can be quickly degraded after the filter tip is discarded.

[0104] The above-mentioned related explanations and descriptions of the embodiments are for the convenience of those skilled in the art to understand and apply the present invention. It is obvious that those familiar with the art can easily make various modifications to these contents and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above-mentioned related explanations and descriptions of the embodiments. Improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A thermoformed composite fiber, characterized in that: The invention comprises water-soluble polymer or hydrophilic polymer fiber processed by melt extrusion, wherein the fiber contains a catalyst for catalyzing the deacetylation of cellulose acetate.

2. The composite fiber according to claim 1, characterized in that The fiber is used as a core layer, and a water-soluble polymer or a hydrophilic polymer is coated on the surface of the core layer as a skin layer to protect the core layer catalyst, thereby forming a skin-core structure fiber.

3. The composite fiber according to claim 1 or 2, characterized in that The fiber is a water-soluble polymer or a hydrophilic polymer, wherein the hydrophilic polymer is naturally degradable polylactic acid, cellulose acetate or polybutylene adipate terephthalate; the water-soluble polymer includes but is not limited to one or more of polyvinyl alcohol, polyethylene glycol, carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyacrylic acid, polyacrylic acid salt, polysulfonic acid, polysulfonic acid salt, polyacrylamide, soluble starch, modified starch and cellulose acetate, preferably one or more of polyvinyl alcohol and polyethylene glycol.

4. The composite fiber according to claim 2, characterized in that The water-soluble polymer or hydrophilic polymer in the cortex includes, but is not limited to, one or more of polyvinyl alcohol, polyethylene glycol, carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyacrylic acid, polyacrylic acid salt, polysulfonic acid, polysulfonic acid salt, polyacrylamide, soluble starch, and modified starch.

5. The composite fiber according to claim 3, characterized in that The alcoholysis degree of the polyvinyl alcohol is 70%-95%, and the viscosity is 3-30 cps; or the molecular weight of the polyethylene glycol is 300-20000, preferably 800-12000.

6. The composite fiber according to claim 1, characterized in that The catalyst is uniformly dispersed in the fiber, and the weight ratio of the catalyst to the fiber is 5%-30%, preferably 15%-25%; and / or The catalyst powder particle size is 10 nm-50 μm, preferably 500 nm-5 μm.

7. The composite fiber according to claim 1 or 6, characterized in that The catalyst is an alkaline material with a pH value greater than 7, used for catalyzing the deacetylation of cellulose acetate, and is an alkaline inorganic substance and / or an alkaline organic small molecule compound.

8. The composite fiber according to claim 7, characterized in that The alkaline inorganic substance includes, but is not limited to, one or a combination of magnesium oxide, magnesium hydroxide, calcium oxide, alkaline aluminum oxide, calcium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, magnesium carbonate, calcium carbonate, sodium bicarbonate, potassium bicarbonate, potassium phosphate, sodium phosphate, magnesium phosphate, calcium phosphate, ammonium hydrogen phosphate, and sodium sulfite; The basic organic small molecule compound includes, but is not limited to, one or a combination of more than one of arginine, lysine, histidine, amino acid polypeptide, sodium citrate, potassium citrate, sodium acetate, potassium acetate, pyridine, morpholine, imidazole, methylamine, ethylamine, diethylamine, triethylamine, diisopropylamine, and 1-acetylguanidine. 9 . The composite fiber according to claim 8 , wherein the catalyst can be used alone or in combination of more than one, and the catalyst is preferably magnesium oxide, magnesium hydroxide, calcium hydroxide, or 1-acetylguanidine.

10. A controllable degradation filter rod, characterized in that: The filter rod is embedded with the composite fiber according to any one of claims 1 to 9.

11. The controllable degradation filter rod according to claim 10, characterized in that: The composite fibers are embedded in the filter rod in a single-line, double-line or multi-line structure.

12. The controllable degradation filter rod according to claim 10 is used in cigarettes, characterized in that: The filter rod is used as a section of the filter structure.

13. The method for preparing a composite fiber according to any one of claims 1 to 9, characterized in that: The fiber material and the catalyst material are uniformly mixed in the form of solid powder, and are melt-extruded through a twin-screw machine to form fibers as the core layer.

14. The method for preparing composite fibers according to claim 13, characterized in that: A layer of water-soluble polymer or hydrophilic polymer is coated on the surface of the core layer by solution dipping as a skin layer to protect the catalyst of the core layer and form a composite fiber.

15. The method for preparing composite fibers according to claim 14, characterized in that: Modulating water-soluble polymers or hydrophilic polymers in the cortex; Polyvinyl alcohol is selected as the water-soluble polymer or hydrophilic polymer in the cortex, the alcoholysis degree is 70%-95%, the viscosity is 3-30cps, and the concentration of the aqueous solution is 3%-20%, preferably 5%-12%; and / or Polyethylene glycol is selected as the water-soluble polymer or hydrophilic polymer in the cortex, with a molecular weight of 300-4000, preferably 800-1200, and a concentration of 10%-30% in the prepared aqueous solution; and / or One of carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose is selected as the water-soluble polymer or hydrophilic polymer in the cortex, with a viscosity range of 30-20000 mPaS and an aqueous solution concentration of 0.5%-5%; and / or Soluble starch is selected as the water-soluble polymer or hydrophilic polymer in the cortex, and the concentration of the aqueous solution ranges from 3% to 10%; and / or Cellulose acetate is selected as the water-soluble polymer or hydrophilic polymer in the skin layer, with a viscosity range of 1.4-1.7 g / dL and a degree of substitution range of 2.0-2.8, preferably 2.3-2.5; the cellulose acetate is dissolved in acetone and then coated on the outside of the core layer, and the concentration of the acetone solution is 3%-20%, preferably 5%-10%.

16. The method for preparing composite fibers according to claim 13, characterized in that: The twin-screw machine melt extrusion processing temperature is 100℃-200℃, and / or The diameter of the melt extruded fiber is 0.1 mm to 1 mm, preferably 0.2 mm to 0.5 mm, and / or The tensile strength of the fiber is greater than 0.1N / tex -1 .

Citation Information

Patent Citations

  • Multi-micropore polyester fiber and preparation method thereof

    CN101144206A

  • Degradable cigarette filter: pill with multilayered coating

    CN102711533A

  • Melt spinning method for high-strength high-modulus polyvinyl alcohol fiber

    CN102797050A

  • Method for preparing low-temperature polyvinyl alcohol water-soluble fiber

    CN110331457A

  • Catalyst introduction process for accelerated deacetylation of cellulose esters

    CN116133537A